2010
DOI: 10.1038/hdy.2010.142
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and genetic correlation between the sexes in a songbird sexual ornament

Abstract: The genetic correlation between the sexes in the expression of secondary sex traits in wild vertebrate populations has attracted very few previous empirical efforts of field researchers. In southern European populations of pied flycatchers, a sexually selected male ornament is also expressed by a proportion of females. Additive genetic variances in ornament size and expression, transmission mechanisms (autosomal vs Z-linkage) and maternal effects are examined by looking at patterns of familial resemblance acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 79 publications
1
61
0
Order By: Relevance
“…The forehead patch size was highly repeatable, indicating high heritability or permanent environmental effects on this trait during the early development. This is in agreement with a previous study that found high heritability for forehead patch size in male pied flycatchers of the Iberian population (Potti & Canal, ). Moreover, the fact that we did not find any correlation between environmental conditions during the prebreeding moult and the size of the forehead patch supports the idea that the forehead patch size is more genetically than environmentally determined.…”
Section: Discussionmentioning
confidence: 97%
“…The forehead patch size was highly repeatable, indicating high heritability or permanent environmental effects on this trait during the early development. This is in agreement with a previous study that found high heritability for forehead patch size in male pied flycatchers of the Iberian population (Potti & Canal, ). Moreover, the fact that we did not find any correlation between environmental conditions during the prebreeding moult and the size of the forehead patch supports the idea that the forehead patch size is more genetically than environmentally determined.…”
Section: Discussionmentioning
confidence: 97%
“…Kiauta 1969). Cases where traits that are under sexual selection in one sex also appear in the opposite sex may result from intralocus sexual conflict (Bonduriansky and Rowe 2005;Poissant et al 2009;Potti and Canal 2011). It should be emphasised, however, that there is a clear wing shape dimorphism between males and females (see also Johansson et al 2009).…”
Section: Evolutionary Divergence In Female Hind Wingsmentioning
confidence: 95%
“…In Iberian populations of pied flycatchers ( Ficedula hypoleuca Pallas, 1764), some females express a forehead patch of pale (white or creamy) feathers similar to that all males display, although often smaller (by a half, on average; Potti & Canal, ). Both genetic (Potti, ; Potti & Canal, ) and functional (Potti & Merino, ; Morales et al ., ) hypotheses have been invoked to explain female expression as well as size of the ‘male’ ornament in these populations.…”
Section: Introductionmentioning
confidence: 99%
“…In Iberian populations of pied flycatchers ( Ficedula hypoleuca Pallas, 1764), some females express a forehead patch of pale (white or creamy) feathers similar to that all males display, although often smaller (by a half, on average; Potti & Canal, ). Both genetic (Potti, ; Potti & Canal, ) and functional (Potti & Merino, ; Morales et al ., ) hypotheses have been invoked to explain female expression as well as size of the ‘male’ ornament in these populations. A preference of males for females displaying large forehead patches has been suggested on the basis of the reported assortative mating with respect to trait size (Potti & Merino, ; Potti & Canal, ) and the signalling of their age and parasite (trypanosome)‐free condition by ornamented females (Potti & Merino, ) although the possibility that assortative mating may be due to reasons other than mate choice cannot be discarded (Burley, ; Roulin, ; Kraaijeveld et al ., ).…”
Section: Introductionmentioning
confidence: 99%